Efeito da espessura da parede no desempenho hidráulico de mangueiras gotejadoras - Schimidt, Ana Paula Russo Assumpção [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Companies in the agricultural sector see a great business opportunity in the Brazilian irrigation sector. A fact proven by the increasing number of companies that has been specializing in importing, reselling and even design and manufacture their own models of drippers. National companies generally work with a single model of dripper that is inserted in the dripperlines with different thicknesses to suit different types of consumers. The current research evaluates the effect of wall thickness on the hydraulic performance of dripperlines. The experiment was conducted in a bench trial in the Laboratory Testing Equipment for Irrigation of Faculty of Agronomic Sciencies UNESP. Four Brazilian manufactured dripperlines (Tiquira, Manari, Amandi and Jurussu) of Petroisa Company were evaluated. The evaluations were done according to the ISO 9261:2004. The parameters determined were coefficient of variation of manufacture, relation pressure x flow, the characteristic equation, wall thickness and inside diameter, the spacing between drippers and hydraulic pressure resistance at room temperature and at 40 oC. As a result, the coefficients of variation of manufactore the specifications of the ISO 9261:2004 standard, except Manari. According to the catalog provided by the manufacturer, the characteristics of the dripperlines equations showed the same values, since the emitters are 2 the same type. This observation does not correspond to the results obtained in the experiment, which demonstrated distinct equations for the different dripperlines used. The results indicated a tendency that one is using the same type of dripper for the same pressure, the larger the wall thickness, the lower the flow rate of the dripper. The other variables had results within established standard, also being in agreement with the values listed in ...

As empresas do setor agrícola vêem na irrigação brasileira uma grande oportunidade de negócio, fato comprovado pelo crescente número de empresas que vem se especializando em importar, revender e até mesmo projetar e fabricar seus próprios modelos de gotejadores. As empresas nacionais, de maneira geral, trabalham com um único modelo de emissor inserido em mangueiras com espessuras diferentes para atender os diferentes tipos de aplicações e consumidores. Com o objetivo de avaliar a interferência da espessura da parede das mangueiras gotejadoras na vazão oferecida pelo emissor foi desenvolvido um experimento no Laboratório de Hidráulica do Departamento de Engenharia Rural da Universidade Estadual Paulista “Júlio de Mesquita Filho” Campus de Botucatu. O trabalho conduzido em uma bancada de ensaio, avaliou quatro mangueiras de fabricação nacional (Tiquira, Manári, Amandi e Jurussu) da empresa Petroisa. As avaliações foram realizadas segundo a norma internacional ISO 9261:2004. Os parâmetros avaliados foram: coeficiente de variação de fabricação, relação vazão x pressão, determinação da equação característica, espessura de parede e diâmetro interno das mangueiras, espaçamento entre emissores e resistência à pressão hidráulica em temperatura ambiente e à temperatura de 40 oC. Como resultado os coeficientes de fabricação das mangueiras atenderam às especificações da norma ISO 9261:2004, com exceção da Manári. S egundo o catálogo fornecido pelo fabricante, as equações características das mangueiras apresentariam os mesmos valores, uma vez que os emissores são do mesmo modelo. Essa observação não correspondeu ao resultado obtido no experimento, que obteve equações distintas para as diferentes mangueiras utilizadas.Observou-se também que ao se utilizar o mesmo modelo de gotejador para uma mesma pressão, quanto maior a espessura ...
Keywords: Irrigação agricola; Irrigação por gotejamento; Agua na agricultura; Equipamento agricola; Irrigation